Effect of High-Density Packing Recycled Aggregate on Concrete Strength Properties - Wathiq S. Albo Ali; Mazin B. Abdulrahman; Ahmed A. Alani; Ruclan B. Lesovik (Tikrit Journal of Engineering Sciences, 2024)
As many residential homes and structures were destroyed or badly damaged because of the military battle in Iraq, it is critical to recycle construction debris widely in the rebuilding and decoration of buildings and infrastructure. This battle resulted in the buildup of massive construction debris, and recycling this waste allows for a cleaner environment. Recycling the construction waste of various installations is an urgent need to decrease the consumption of natural materials and landfills of construction waste, and as a result reduce the environmental pollution. Therefore, this study is a local focus on using concrete debris to obtain high packing density recycled coarse and fine aggregates in various fractions of (0.16 mm - 10 mm) by selecting high-density packing materials that was developed by Kharkhadin A.N in laboratories of Belgorod State Technical University in Russia to preparing of reference mix from ordinary density recycled aggregate. The new concrete samples for two concrete mixtures were prepared, to identify and study the important specifications. Models of cubes and standard prisms were prepared to evaluate the compressive strength and the splitting tensile strength. Also, the modulus of rupture and the unit weight were conducted. The results indicated an increase in the concrete’s mechanical properties using the high-packing density recycled aggregate. The obtained compressive strength, splitting tensile strength and modulus of rupture were (49) MPa, (3.6) MPa, and (7.1) MPa compared with a reference mix (39) MPa, (3.3) MPa and (6.3) MPa, respectively. The reference mix corresponding properties were (39) MPa, (3.3) MPa, and (6.3) MPa, respectively. Also the values of an oven-dry density were (2340) kg/m3 compared with the reference mix (2260kg/m³). These results proved that increasing the packing density of recycled aggregate enhanced the concrete’s strength properties.